The biochemistry of melanogenesis: an insight into the function and mechanism of melanogenesis-related proteins - Wang, Feifei; Ma, Wenjing; Fan, Dongjie; Hu, Jing; An, Xiaohong; Wang, Zuding (Frontiers in Molecular Biosciences, 2024)
Melanin is an amino acid derivative produced by melanocyte through a series of enzymatic reactions using tyrosinase as substrate. Human skin and hair color is also closely related to melanin, so understanding the mechanisms and proteins that produce melanin is very important. There are many proteins involved in the process of melanin expression, For example, proteins involved in melanin formation such as p53, HNF-1α (Hepatocyte nuclear factor 1α), SOX10 (Sry-related HMg-Box gene 10) and pax3 (paired box gene 3), MC1R(Melanocortin 1 Receptor), MITF (Microphthalmia-associated transcription factor), TYR (tyrosinase), TYRP1 (tyrosinase-related protein-1), TYRP2 (tyrosinase-related protein-2), and can be regulated by changing their content to control the production rate of melanin. Others, such as OA1 (ocular albinism type 1), Par-2 (protease-activated receptor 2) and Mlph (Melanophilin), have been found to control the transfer rate of melanosomes from melanocytes to keratinocytes, and regulate the amount of human epidermal melanin to control the depth of human skin color. In addition to the above proteins, there are other protein families also involved in the process of melanin expression, such as BLOC, Rab and Rho. This article reviews the origin of melanocytes, the related proteins affecting melanin and the basic causes of related gene mutations. In addition, we also summarized the active ingredients of 5 popular whitening cosmetics and their mechanisms of action.